Pesticide monitoring in inshore waters of the Great Barrier Reef using both time-integrated and event monitoring techniques (2010-2011) - Kennedy, K.; Devlin, M.; Bentley, C.; Paxman, C.; Chue, K.L.; Mueller, J. (The University of Queensland, 2012)
The report details pesticide monitoring activities carried out utilising a combination of passive sampling and grab sampling techniques in the Great Barrier Reef Marine Park as part of the Reef Rescue Marine Monitoring Program (MMP). The MMP was implemented to evaluate changes in water quality in the Great Barrier Reef (GBR) and the status of key ecosystems under the Reef Water Quality Protection Plan (RWQPP) 2003 (which was further updated in 2009).
Keywords: Pesticides; Environmental monitoring; Sampling techniques; Programme evaluation; Water quality; Evaluation; Water conservation; Environmental impact studies; Ecosystems; Processes; Water quality; Reef-wide